Opfernarrative in transnationalen Kontexten (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
This edited volume examines the representation of victims beyond the categories of the “victim cult,” self-victimization, and the victim–perpetrator dichotomy. Adopting a transnational perspective, it mainly considers literature written after 1989, leveraging concepts of dialogical and multidirectional memory to facilitate differentiated perspectives in the politics of memory regarding the highly charged figure of the victim